1990
DOI: 10.1128/mcb.10.2.569
|View full text |Cite
|
Sign up to set email alerts
|

Corrective recombination of mouse immunoglobulin kappa alleles in Abelson murine leukemia virus-transformed pre-B cells.

Abstract: Previous characterization of mouse immunoglobulin K gene rearrangement products cloned from murine plasmacytomas has indicated that two recombination events can take place on a single K allele (R. M. Feddersen and B. G. Van Ness, Proc. Natl. Acad. Sci. USA 82:4792-4797, 1985; M. A. Shapiro and M. Weigert, J. Immunol. 139:3834-3839, 1987). To determine whether multiple recombinations on a single K allele can contribute to the formation of productive V-J genes through corrective recombinations, we have examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…One possibility extends the suggestion by Shapiro and Weigert (27) that inversional rearrangements might provide a means by which more distal VK gene segments can be repositioned closer to Ja segments, thereby increasing their probability for recombination . This speculation is consistent with the findings that multiple, sequential VK rearrangements can occur on a single chromosome (26,27,30) . Considering the size of the Va4 family, its central position within the VK region, and the ability of at least some Vu4 genes to rearrange by inversion, the Vic4 family may play a special role in bringing JK segments and distal VK genes together for recombination .…”
supporting
confidence: 92%
“…One possibility extends the suggestion by Shapiro and Weigert (27) that inversional rearrangements might provide a means by which more distal VK gene segments can be repositioned closer to Ja segments, thereby increasing their probability for recombination . This speculation is consistent with the findings that multiple, sequential VK rearrangements can occur on a single chromosome (26,27,30) . Considering the size of the Va4 family, its central position within the VK region, and the ability of at least some Vu4 genes to rearrange by inversion, the Vic4 family may play a special role in bringing JK segments and distal VK genes together for recombination .…”
supporting
confidence: 92%
“…56,72 Productive V-J rearrangements have been recovered from both excision circles 73 and reciprocal products. 74,75 Single cell PCR studies showed that the frequency of + / + in individual B cells is approximately 10%. 76,77 Lambda L chain rearrangements in murine and human B cells were also frequently allelically included.…”
Section: Secondary Light Chain Rearrangementsmentioning
confidence: 99%
“…Nevertheless, a transgenic K chain present in the cytoplasm did not shut offthe endogenous K gene rearrangement (5). It is also reported that corrective V -J recombinations, with displacement of the nonproductive K gene, occur with a significant frequency in clonal cell lines (7). This suggests that secondary recombinations of one allele may continue unless prevented by the feedback inhibition of a functional product.…”
mentioning
confidence: 99%